2020
DOI: 10.7717/peerj.9571
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of the extra-pair mating behaviour of the pied flycatcher in Western Siberia

Abstract: Males and females take part in extra-pair copulations in most socially monogamous bird species. The mechanisms leading to the frequent occurrence of extra-pair offspring in socially monogamous couples are strongly debated and unresolved, and they are often difficult to distinguish from one another. Most hypotheses explaining the evolution of extra-pair reproduction suggest selective and adaptive scenarios for their origination and persistence. Is extra-pair paternity a heritable trait? We evaluated the heritab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 99 publications
(191 reference statements)
1
6
0
Order By: Relevance
“…EPP would not be an individual trait but the result of the interaction of individuals in a varying and fluid social context affecting behaviours operating during a brief period of time each season (Beck et al 2020). Our study supports the conclusion from another study showing extremely low heritability estimates for EPP (Grinkov et al 2020). Most traits linked to EPY are individually variable from year to year, such as age and breeding phenology.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…EPP would not be an individual trait but the result of the interaction of individuals in a varying and fluid social context affecting behaviours operating during a brief period of time each season (Beck et al 2020). Our study supports the conclusion from another study showing extremely low heritability estimates for EPP (Grinkov et al 2020). Most traits linked to EPY are individually variable from year to year, such as age and breeding phenology.…”
Section: Discussionsupporting
confidence: 87%
“…To ascertain the importance of individual traits for EPP it is necessary to estimate repeatability of individuals across different pair contexts as caused by mate changes between seasons. Two recent studies do indeed show low EPP repeatability estimates across seasons, namely in Blue Tits Cyanistes caeruleus (Beck et al 2020) and in Pied Flycatchers Ficedula hypoleuca (Grinkov et al 2020), underlining that we are dealing with a very phenotypically labile trait.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Equivalent attention has also been given towards intersexual pleiotropic effects, where female extra‐pair behaviour may be linked with a trait which benefits male reproductive success; these studies have found little support in captivity (Wang et al 2020), or in wild populations (Zietsch et al 2015, Reid and Wolak 2018). Where quantitative genetic studies have sought to demonstrate a heritable basis for male extra‐pair behaviour, required for intersexual pleiotropy to drive female extra‐pair behaviour, estimates are low (Reid et al 2011, Reid and Wolak 2018, Grinkov et al 2020). However, Dobson et al (2023) suggested that the inclusion of social partner indirect genetic effects (those derived from the behaviour of another) improved model fit for the heritability of both male and female extra‐pair behaviour, implying a role for the wider social environment in the plasticity of extra‐pair behaviour.…”
Section: Discussionmentioning
confidence: 99%